SPEECH FUNCTION IN ‘YEAH MAHASISWA’ TWEETS - Rondang Donna Berhnitha Manalu; Elia Masa Gintings (State University of Medan, 2014)
ABSTRACT This study deals with speech function in ‘Yeah Mahasiswa’ tweets. The research was conducted by using descriptive qualitative method. The data were collected from the twitter account of Yeah Mahasiswa which chosen purposively. The findings of the research show that there are 105 clauses which consist of 4 speech functions, Statement (84), Question (11), Command (6), andOffer (4). The most dominant type of speech function used by Yeah Mahasiswa wasstatement because it tended to give information in its interaction through its tweets. The occurrence of the dominant speech function due to the context of situation, covering field, tenor and mode. Keyword: Speech Function, Twitter